Strategi Internalisasi Pencegahan Kekerasan Menuju Pengasuhan yang Humanis (Studi di Pondok Pesantren Darul Ulum Magetan) - Anisa Deny Setiawati; Emmilia Rusdiana; Nurul Hikmah; Syahid Akhmad Faisol; Aditya Wiguna Sanjaya (Integralistik, 2026)
Violence still occurs in the education sector, as well as in Islamic boarding schools. Violence can occur due to a lack of knowledge among students, guardians, and administrators. In contrast, one of the determinants of efforts to eliminate violence in Islamic boarding schools is the policy within the Islamic boarding school environment. One of the spearheads of violence that appears in the Islamic boarding school environment is the parenting pattern in the relationship between the Islamic boarding school and students. This activity aims to identify knowledge about violence and Islamic boarding school policies in preventing violence, with the specific objective of being the initial step in compiling patterns of Islamic boarding school policies. Data collection, based on Focus Group Discussion (FGD) activities, involved 20 students, administrators, parents of students, and caretakers of an Islamic boarding school. The FGD produced patterns of violence and agreement in forming efforts to harmonize various parties in activities at Islamic boarding schools. This activity resulted in increased knowledge about violence and prevention efforts, as well as a commitment from administrators and caretakers to compile humanist Islamic boarding school care management patterns in accordance with the characteristics of Islamic boarding schools and other relevant government policies.